2013 Ukraine Enterprise Survey : Country Highlights - World Bank; International Finance Corporation (Washington, DC, 2014)
The World Bank interviewed a representative sample of the private sector, composed of 1,002 establishments, between January and November 2013. The enterprise survey covers several aspects of the business environment as well as performance measures for each firm. This report presents following highlights from the survey: firm performance indicators point to a significant deterioration over the last five years; several access to credit indicators also reveal a deterioration over time; the time tax imposed by regulations has increased despite improvements in selected indicators; Ukrainian firms faced a significant increase in the level of corruption; female inclusion in the private economy decreased over the last five years; and access to finance and corruption were the top obstacles chosen by the business community.